Current Challenges and Personalized Treatment in Cardiovascular Disease (MDPI - Multidisciplinary Digital Publishing Institute, 2024)
Cardiovascular disease is a leading cause of death worldwide among the various cardiac pathologies that directly or indirectly affect the quality of life of patients. The many innovative diagnostic and treatment approaches for heart disease could also lead to a new era in medicine and cardiovascular disease. Minimally invasive cardiac surgery minimizes surgical stress, and its use is a growing trend in cardiac surgery. A current challenge in the management of cardiovascular disease is combining known clinical practice with innovative diagnostic methods and treatment.